(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study was conducted for the detection of persistence of Maternally derived antibody (MDA) as well as the comparative evaluation of antibody production of nine different NDV vaccines in layer chickens in the Department of Microbiology and Hygiene, Bangladesh Agricultural University, Mymensingh during the period from July to December 2008. A total of 55 layer chicks (ISA Brown breed) were divided into eleven groups each consisting of five birds of which odd number groups were vaccinated primarily with Nobilis® MA5+Clone 30, Avipro® ND-IB HB1, Cevac® BIL, Newcastle-Bronchitis Vaccine Fortdoge® and Avipro® ND LaSota vaccine respectively at day 5 of age and secondarily with Nobilis® ND Clone30, Avipro® ND LaSota, Cevac® New L, Newcastle Disease Vaccine Fortdoge® and Avipro® ND LaSota vaccine respectively at day 21 of age by single eye instillation and even number groups were vaccinated with the same vaccines respectively by double eye instillation following the same schedule. Again group 9 and group 10 were also vaccinated with RDV at 60 days of age through intramuscular route. Group 11 was kept as unvaccinated control. Sera samples were collected after 10 days of each vaccination and at day 5, 15, 20, 31 of age from unvaccinated control and subjected to HI test for the determination of antibody titres. It was observed that after primary vaccination the mean of HI titres of double eye vaccinated groups differed significantly (P<0.01). Overall analysis of mean of HI titres of double eye vaccinated groups revealed that there were significant increases (P<0.01) in HI titres in groups 8 (891.44±228.97) and 10 (861.66±140.21) compared to other groups. It was observed that secondary vaccination produced higher immune response compared to primary vaccination in case of all the vaccinated groups and double eye vaccination produced higher immune response compared to single eye vaccination in case of all the vaccinated groups. It was also observed that following vaccination with RDV in groups 9 and 10, HI titres increased significantly (P<0.01) which indicated that group 10 (1204.30±280.43 ) produced significantly higher antibody titres than group 9 (966.74±144). Maternal antibody was high (483.37±181.01) at day 5 of age and persisted to a minimal level (8.00±0.00) until the age of day 20 and almost disappears (≤4±0) at day 31 of age. From the present research it may be concluded that LaSota strain produced higher immune response than Clone 30 and B1 strain, Fortdose® and Avipro® vaccine produced higher immune response than all other vaccines and vaccination with lentogenic strains followed by mesogenic strain produced higher antibody titers used in this study. Keywords: Immune response; Newcastle disease; Vaccines; Layer chickens DOI: 10.3329/jbau.v7i2.4743 J. Bangladesh Agril. Univ. 7(2): 329-334, 2009